2021
DOI: 10.1152/ajplung.00046.2020
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing mast cells improves acute lung injury after orthotopic liver transplantation via promotion of apoptosis in polymorphonuclear neutrophils

Abstract: Aims: Postoperative pulmonary complications including acute lung injury (ALI) and acute respiratory distress syndrome have contributed to the mortality and morbidity of orthotopic liver transplantation (OLT) with unclear mechanisms. Mast cells (MCs) and polymorphonuclear neutrophils (PMNs) are the main inflammatory cells and participants in the process of ALI. The present study was designed to investigate the role of MCs and PMNs and their potential relation to ALI following OLT. Main Methods: Rat orthotopic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Therefore, these results indicated that PHI treatment suppressed the inflammatory response in LPS-induced BEAS-2B cells. (18). The apoptotic effects of PHI on BEAS-2B cells were confirmed by TUNEL assay and western blot analysis.…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, these results indicated that PHI treatment suppressed the inflammatory response in LPS-induced BEAS-2B cells. (18). The apoptotic effects of PHI on BEAS-2B cells were confirmed by TUNEL assay and western blot analysis.…”
Section: Resultsmentioning
confidence: 83%
“…A variety of immune cells which include macrophages, neutrophils, mast cells, epithelial cells, and T cells are involved in acute lung inflammation [ 20 , 21 ]. Recently, there has been accumulating evidence indicating that alveolar macrophages (AMs) perform critical functions in the ALI/ARDS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years it has become clear that the digestive organs and their associated microbial partners, together with the enteric neuronal and immune systems, play critical roles in physiology that reach far beyond the traditional gastrointestinal functions of nutrient absorption and water/electrolyte balance (37,38). An emerging picture of the importance of the gut-brain axis, gut-lung-axis, etc.…”
Section: Ajp-gastrointestinal and Liver Physiologymentioning
confidence: 99%